2021
DOI: 10.1177/23094990211002294
|View full text |Cite
|
Sign up to set email alerts
|

Early postoperative straight leg raise is associated with shorter length of stay after unilateral total knee arthroplasty

Abstract: Purpose: Shorter length of stay (LOS) after total knee arthroplasty (TKA) is cost-effective. Straight leg raise (SLR) is a common exercise prescribed after TKA, but the significance of early postoperative SLR is unknown. The primary aim of this study is to evaluate the association between early postoperative SLR and LOS. Secondary aims are to explore associations among early postoperative SLR, time to ambulation, and time to stairs climbing and identify factors related to postoperative SLR. Methods: 888 TKAs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
2
5
1
Order By: Relevance
“…19 In their study, Suh et al found that SLR was associated with shorter LOS and faster time to ambulation. 23 There were no statistically significant differences in patients' ability to actively perform SLR between groups in our study, which suggests that although the ACB likely confers some motor blockade, it is not enough to cause any significant weakness.…”
Section: Range Of Motion and Slrcontrasting
confidence: 51%
“…19 In their study, Suh et al found that SLR was associated with shorter LOS and faster time to ambulation. 23 There were no statistically significant differences in patients' ability to actively perform SLR between groups in our study, which suggests that although the ACB likely confers some motor blockade, it is not enough to cause any significant weakness.…”
Section: Range Of Motion and Slrcontrasting
confidence: 51%
“…Ishii et al. found no correlation of SLR to standing up and walking [ 16 ]; however, a more recent study found that the ability to perform an SLR on POD 1 led to decreased time to ambulation, stair climbing, and a decrease in length of stay in the hospital [ 17 ]. Our study demonstrated a statistically significant difference in the patient’s ability to perform an SLR on POD 1, with 100% of patients in the NT group able to SLR while only 77% of patients in the T group were able to SLR ( P < .001).…”
Section: Discussionmentioning
confidence: 99%
“…Early rehabilitation in geriatric burn patients is crucial in mitigating complications, reducing duration of hospital stay, improving over-all strength, maximizing functional outcome, and quality of life. 9 Bedside exercises, such as straight leg raises, were essential in promoting strengthening of the quadriceps muscles, improving pain control, and promoting better functional recovery over time.…”
Section: Discussionmentioning
confidence: 99%